Α‐1‐Antitrypsin detected by MALDI imaging in the study of glomerulonephritis: Its relevance in chronic kidney disease progression. Issue 11 (14th March 2016) - Smith, Andrew; L'Imperio, Vincenzo; De Sio, Gabriele; Ferrario, Franco; Scalia, Carla; Dell'Antonio, Giacomo; Pieruzzi, Federico; Pontillo, Claudia; Filip, Szymon; Markoska, Katerina; Granata, Antonio; Spasovski, Goce; et al.
Abstract : Idiopathic glomerulonephritis (GN), such as membranous glomerulonephritis, focal segmental glomerulosclerosis (FSGS), and IgA nephropathy (IgAN), represent the most frequent primary glomerular kidney diseases (GKDs) worldwide. Although the renal biopsy currently remains the gold standard for the routine diagnosis of idiopathic GN, the invasiveness and diagnostic difficulty related with this procedure highlight the strong need for new diagnostic and prognostic biomarkers to be translated into less invasive diagnostic tools. MALDI‐MS imaging MALDI‐MSI was applied to fresh‐frozen bioptic renal tissue from patients with a histological diagnosis of FSGS ( n = 6), IgAN, ( n = 6) and membranous glomerulonephritis ( n = 7), and from controls ( n = 4) in order to detect specific molecular signatures of primary glomerulonephritis. MALDI‐MSI was able to generate molecular signatures capable to distinguish between normal kidney and pathological GN, with specific signals ( m/z 4025, 4048, and 4963) representing potential indicators of chronic kidney disease development. Moreover, specific disease‐related signatures ( m/z 4025 and 4048 for FSGS, m/z 4963 and 5072 for IgAN) were detected. Of these signals, m/z 4048 was identified as α‐1‐antitrypsin and was shown to be localized to the podocytes within sclerotic glomeruli by immunohistochemistry. α‐1‐Antitrypsin could be one of the markers of podocyte stress that is correlated with the development of FSGS due to both an excessive loss and a hypertrophy of podocytes.